Children's use of public spaces and the role of the adult – a comparison of play ranging in the UK, and the leikkipuisto (Play Parks) in Finland. Issue 1 (2nd January 2018) - King, Pete; Sills-Jones, Polly
ABSTRACT: Globally, public spaces are designated for children and young people to use within their communities. In the UK, these spaces have historically been playing-fields and parks with fenced playgrounds. The adult presence within these public spaces has evolved; from the supervisory role of the 'park keeper' to the active engagement of Playworker and more recently Play Rangers. For over 100 years in Finland, leikkipuisto have provided extensive, child-focused play parks; balancing man-made and natural resources, to provide a vast range of affordances. Furthermore, the adult – the Ohjaaja – is integral to the provision. This paper draws on the experiences of the authors, and considers how the Play Ranger and the Ohjaaja have similar roles in supporting children and young people to play. This is discussed in relation to Kyttä's four hypothetical environments: Bullerby, Glasshouse, Wasteland and Cell [2004]. The extent of children's independent mobility and the number of actualized affordances as criteria for child-friendly environments. Journal of Environmental Psychology, 24, 179–198. and historical and funding differences between the UK and Finland.